GEOSPATIAL MODELLING AND SOCIOECONOMIC PROFILING OF FUELWOOD CONSUMPTION PATTERNS IN DOROK DISTRICT, PLATEAU STATE, NIGERIA - Choji, Vincent; Yakubu, Kyalak; David, Barnabas; Chris, Magnus; Ifegbesan, Ayodeji (FUDMA Journal of Sciences, 2026)
Household reliance on biomass energy is a major driver of land-cover change in rural Nigeria. This study used socio-economic surveys (n = 150), statistical analyses, and NDVI-based Land Use and Land Cover (LULC) assessment from multi-temporal Landsat imagery (1990–2025) to examine fuelwood consumption and vegetation dynamics in Dorok District, Plateau State. Results show high fuelwood use, with mean daily consumption of 14.27 kg per household (1.78 kg per capita). Female-headed households consumed more than male-headed households, and consumption increased with household size, while education had minimal effect. NDVI analysis revealed that vegetation loss was not significantly driven by fuelwood harvesting, with broader land-use changes as the dominant factor. The 2025 LULC classification showed high reliability: water bodies and built-up areas were mapped most accurately, while vegetation classes had moderate accuracy due to heterogeneous landscapes. Overall Accuracy (85%) and Kappa (0.77) confirm the dataset’s robustness for spatial and ecological analysis. These findings highlight the need for gender-sensitive energy interventions, adoption of alternative household fuels, and community-based conservation. The study demonstrates the value of validated LULC datasets for monitoring landscape change, understanding vegetation dynamics, and informing sustainable land management in rural Nigeria.
Keywords: Biomass Energy Dependence; Socio-Demographic Determinants; Remote Sensing and NDVI; Rural Household Energy